4-OI Attenuates Carbon Tetrachloride-Induced Hepatic Injury via Regulating Oxidative Stress and the Inflammatory Response - Li, Ruidong; Yang, Wenchang; Yin, Yuping; Ma, Xianxiong; Zhang, Peng; Tao, Kaixiong (Frontiers in Pharmacology, 2021)
The liver is an important metabolic organ, and acute liver injury (ALI) is potentially lethal. Itaconate, a metabolic intermediate from the tricarboxylic acid cycle, showed emerging anti-oxidative and anti-inflammation properties and an accumulating protective effect in multiple diseases, but its role in ALI still needs to be further explored. Here we established an ALI model induced by carbon tetrachloride in mice. Our results showed that 4-Octyl itaconate (OI), a derivate of itaconate, mitigated hepatic damage by improving liver function, reducing histopathological damage, and decreasing the death of hepatocytes. Additionally, OI decreased myeloperoxidase and thiobarbituric acid reactive substances (TBARS) levels in the ALI model. OI also inhibited the inflammatory response by reducing pro-inflammatory cytokine secretion (IL-6, TNF-α, IL-1β, and MCP-1) and infiltration of macrophages and neutrophils in the ALI model. However, administration of ML385, a specified Nrf2 inhibitor, eliminated the protective properties of OI in the CCl4-induced liver injury model by increasing hepatic damage and oxidative stress. Furthermore, OI increased the expression and nuclear translocation of Nrf2 and elevated the expression of heme oxygenase-1 and NAD(P)H quinone oxidoreductase 1, while knockdown of Nrf2 eliminated these effects in murine hepatocyte NCTC 1469 under CCl4 treatment. Moreover, we found that OI reduced serum High-mobility group box 1 (HMGB1) levels in CCl4-treated mice. Finally, OI inhibited nuclear translocation of factor-kappa B (NF-𝜅B) and inflammatory cytokine production in murine macrophages. In conclusion, these results indicated that OI ameliorated CCl4-induced ALI by mitigating oxidative stress and the inflammatory response. The possible mechanism was associated with the elevation of Nrf2 nuclear translocation and inhibition of HMGB1 mediated the nuclear translocation of NF-𝜅B.